2022
DOI: 10.1111/apt.17114
|View full text |Cite
|
Sign up to set email alerts
|

Letter: a promising Helicobacter pylori regimen ‐ vonoprazan‐based therapy

Abstract: LINKED CONTENT This article is linked to Ang et al papers. To view these articles, visit https://doi.org/10.1111/apt.17070 and https://doi.org/10.1111/apt.17133

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The crude eradication rate of VA dual therapy was 87.5% by intention-to-treat (ITT) analysis and 89.6% by per-protocol (PP) analysis ( 7 ). VA dual therapy is considered as a promising H. pylori regimen because of its high efficacy, low side effects, and avoidance of unnecessary antibiotic use ( 8 ). However, the efficacy and safety of VA dual therapy in other regions remain uncertain, thus requiring the regimen to be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…The crude eradication rate of VA dual therapy was 87.5% by intention-to-treat (ITT) analysis and 89.6% by per-protocol (PP) analysis ( 7 ). VA dual therapy is considered as a promising H. pylori regimen because of its high efficacy, low side effects, and avoidance of unnecessary antibiotic use ( 8 ). However, the efficacy and safety of VA dual therapy in other regions remain uncertain, thus requiring the regimen to be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…In the US trial the proportion was calculated as at least 95% 30 . VA dual therapy if optimized has the potential advantages of high efficacy, safety, avoidance of unnecessary antibiotic use, and minimal impact on gut microbiota 31,32 . The experience with VA dual therapy so far suggests that it may need to be optimized in different regions before it can be widely used for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori eradication could increase the alpha diversity indexes, decrease the microbial interactions, alter microbial community structure and microbial community structures in short-term and long-term follow-ups, which was supported by a systematic review and meta-analysis by Guo et al It is still controversial regarding whether H. pylori eradication could restore gastric microbiota to uninfected status. Vonoprazan-amoxycillin (VA) dual therapy is a promising H. pylori regimen because of its high efficacy, safety and the avoidance of unnecessary antibiotics use (Hu and Lu, 2022). Hu et al further demonstrated that the alteration of the gut microbiota induced by the VA dual therapy was restored at the confirmation time point (1 month after eradication), which indicated that the VA dual therapy has minimal negative effects on the gut microbiota.…”
Section: H Pylori Pathogenesismentioning
confidence: 99%
“…It is still controversial regarding whether H. pylori eradication could restore gastric microbiota to uninfected status. Vonoprazan- amoxycillin (VA) dual therapy is a promising H. pylori regimen because of its high efficacy, safety and the avoidance of unnecessary antibiotics use ( Hu and Lu, 2022 ). Hu et al.…”
Section: The Influence Of H Pylori Infection or Er...mentioning
confidence: 99%